Neonatal vitamin K prophylaxis in Great Britain and Ireland: the impact of perceived risk and product licensing on effectiveness. Issue 9 (30th May 2007) - Busfield, Alison; McNinch, Andrew; Tripp, John
Abstract : Objective: To determine current use of vitamin K (VK) prophylaxis in newborns and review the efficacy and effectiveness of regimens used. Design: Efficacy and effectiveness calculated using current practice details, data from Southern Ireland and two previous surveys, together with contemporaneous studies of vitamin K deficiency bleeding (VKDB). Setting: Current survey: United Kingdom (Great Britain and Northern Ireland). Efficacy and effectiveness tables: United Kingdom and Southern Ireland. Main outcome measures: Current VK prophylaxis following uncomplicated term deliveries. Relative risk of VKDB calculated for the VK actually received and for "intention to treat". Results: Questionnaire response rate 95% (n = 243), all recommending VK prophylaxis. No association between unit size and route of administration. For uncomplicated term deliveries, 60% recommended intramuscular (IM) prophylaxis, 24% oral and 16% offered both routes without bias. All units offering IM gave a single dose, mostly 1 mg Konakion Neonatal. Oral regimens showed more variation: two thirds gave 2 mg (range 0.5–2 mg), the number of doses ranged from 1 to 11 and many used preparations off-licence or the unlicensed Orakay. IM prophylaxis, if given, provided the best protection (most efficacious) against VKDB. However, on an intention-to-treat basis (effectiveness), there is no statistically significant difference between the risks of VKDB after intended IM VK and after oral prophylaxis intended to continue beyond a week. Conclusions: Although the principles of VK prophylaxis is now accepted by all, there is no uniformity in practice. Omission of prophylaxis appears to be a greater problem for IM than for multi-dose oral prophylaxis, affecting overall effectiveness.